Indeks Kesesuaian Wisata Bahari Kategori Rekreasi Pantai di Pantai Balangan, Kabupaten Badung, Bali - Sherina Oktafianti; I Wayan Darya Kartika; I Wayan Restu (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2021)
This research was conducted to determine the suitability of marine tourism conditions for the beach recreation category to preserve sustainable marine tourism. The IKW data collection used the purposive sampling method. This research was divided into 3 observation stations with a sampling distance of 10 m from the shoreline to the sea. Determination of the marine tourism suitability index of beach recreation used the suitability matrix analysis by considering 10 parameters such as water depth, water brightness, beach type, beach width, beach slope, current velocity, water bottom material, coastal land cover, hazardous biota, freshwater availability. Water brightness, current velocity, beach widh, water depth and hazardous biota parameters data collection is carried out with 3 repetitions, whereas the other parameters are carried out without repetition. The parameter conditions for the IKW for beach recreation at Balangan beach had a white sand type of beach, beach width 28 m, the water bottom material is sand, water depth 0,66 m, water brightness 73%, current velocity 29 cm/s, beach slope 7,9°, coastal land cover is an open field, without hazardous biota, and freshwater availability 0,075 km. The results were obtained from the calculation of the IKW for beach recreation tourism at station I with a value of 2,92, station II 2,80, and station III 2,92. The result showed that all 3 stations were categorized as a very suitable category which indicates that Balangan Beach is very suitable as a beach recreation tourism object and can be further developed in its management.